Sexuality Discourses: Indexical Misrecognition and the Politics of Sex - Barrett, Rusty; Hall, Kira (Annual Review of Anthropology, 2024)
This review of research on sexuality discourses directs attention to the patterns of indexical disalignment that have facilitated the global rise of transphobic, homophobic, and misogynist discourses. Over the last two decades, scholarship in the area of language and sexuality has focused primarily on patterns of alignment in the community-based indexical production of social personae, a necessary move for establishing the discursive agency, and indeed humanity, of LGBTQ+ groups. The focus of this review, however, is not alignment but disalignment, for it is in the clash of indexical systems that sexual ideologies take root. Specifically, the article focuses on acts of misrecognition that arise at the boundaries of indexical meaning, identifying practices such as indexical inoculation, indexical presumption, and indexical denial. The review is designed to provoke future research on misrecognition as contextualized social practice, a turn we believe imperative for uncovering the power-laden infrastructure of sexuality discourses.
Keywords: Indexicality; Misrecognition; Sexuality; Gender